Plant-Feeding Mites in Citrus - L. M. Diepenbrock; J. D. Burrow; D. Carrillo (EDIS)
This document discusses the identification of common citrus mites. Written by L. M. Diepenbrock, J. D. Burrow, and D. Carrillo and published by the UF/IFAS Entomology and Nematology Department; 2 pp. https://edis.ifas.ufl.edu/in1374